2014
DOI: 10.1080/17290376.2014.985701
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and reproductive health perceptions and practices as revealed in the sexual history narratives of South African men living in a time of HIV/AIDS

Abstract: The frequent positioning of men's sexual risk-taking as driving the HIV/AIDS epidemic in South Africa has triggered interest in men's sexual and reproductive health (SRH) perceptions, attitudes, and practices. Much research, however, presents men as a homogenous group, and focuses on the quantifiable aspects of male sexual behaviors, providing an inadequate basis for understanding men's SRH needs and addressing the gendered aspects of HIV prevention. This study used sexual history narratives to yield more nuan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 35 publications
0
47
0
Order By: Relevance
“…Long-term ART adherence may be enhanced by supporting a more holistic approach to health care within vulnerable communities such as civil society organisations addressing mental health, violence, and substance abuse problems within communities (Stall et al 2003). Men were less open to discuss their difficulties adhering to ART, which is congruent with society’s often routine depiction of men as invulnerable, and a general perception that sexual and reproductive health (SRH) clinics are women’s domain; this can hinder men acknowledging health risks and seeking SRH care (Stern, Rau, & Cooper, 2014). Indeed, several studies in Southern Africa have found that men are more likely than women to delay ART (Cornell, McIntyre, & Myer, 2011) and die of AIDS as a result (Mills et al 2009), and have a higher risk of loss to ART follow-up (Meloni et al, 2014; Wandeler et al, 2012).…”
Section: Discussionmentioning
confidence: 85%
“…Long-term ART adherence may be enhanced by supporting a more holistic approach to health care within vulnerable communities such as civil society organisations addressing mental health, violence, and substance abuse problems within communities (Stall et al 2003). Men were less open to discuss their difficulties adhering to ART, which is congruent with society’s often routine depiction of men as invulnerable, and a general perception that sexual and reproductive health (SRH) clinics are women’s domain; this can hinder men acknowledging health risks and seeking SRH care (Stern, Rau, & Cooper, 2014). Indeed, several studies in Southern Africa have found that men are more likely than women to delay ART (Cornell, McIntyre, & Myer, 2011) and die of AIDS as a result (Mills et al 2009), and have a higher risk of loss to ART follow-up (Meloni et al, 2014; Wandeler et al, 2012).…”
Section: Discussionmentioning
confidence: 85%
“…Finally, one study with men in an urban slum in Uganda found the fear of discrimination on men’s HIV testing was further compounded by a fear that they would lose opportunities for work, thus compromising their role as provider [36]. In only one study in South Africa, in cases where men felt positive recognition for testing from the community, did men’s masculine notion of respectability serve as facilitator to testing [40]. …”
Section: Resultsmentioning
confidence: 99%
“…Six studies focused on the social construction of men as mentally and physically strong, and self-reliant, which reportedly reduced men’s willingness to access HIV testing in five studies [30, 31, 36, 38, 40], and served as motivation for HIV testing in one study [ 41]. In Botswana [38 ] and Ugandan mining communities [30, 31 ], men felt the ability to delay an HIV test was a sign of bravery, resilience, and strength.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations